2018
DOI: 10.14236/ewic/hci2018.212
|View full text |Cite
|
Sign up to set email alerts
|

Alexa, Emotions, Privacy and GDPR

Abstract: We exist in a world where emotional expression is a central facet of what makes us human. It allows us to interact richly with others and aids us in functioning as a society. Affective computing, also known as artificial emotional intelligence is the area of study that seeks to enable the development of systems and devices with the capacity to understand and replicate these human affects. The race is on to develop intelligent computing systems that can mimic human interaction and also emulate and convince huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Other similar assistants are Google's Assistant and Apple's Siri. Studies focusing on the adoption of digital assistants have identified several variables that are associated with the intended or actual usage of these recent technologies: relative advantage, complexity, emotions [32], performance, and price [33], as well as privacy concerns [34].…”
Section: Overview Of Current Researchmentioning
confidence: 99%
“…Other similar assistants are Google's Assistant and Apple's Siri. Studies focusing on the adoption of digital assistants have identified several variables that are associated with the intended or actual usage of these recent technologies: relative advantage, complexity, emotions [32], performance, and price [33], as well as privacy concerns [34].…”
Section: Overview Of Current Researchmentioning
confidence: 99%